Best Practices for Cardiovascular Disease Prevention in Rheumatoid Arthritis: A Systematic Review of Guideline Recommendations and Quality Indicators. Issue 2 (February 2015) - Barber, Claire E. H.; Smith, Alexa; Esdaile, John M.; Barnabe, Cheryl; Martin, Liam O.; Faris, Peter; Hazlewood, Glen; Noormohamed, Raheem; Alvarez, Nanette; Mancini, G. B. John; Lacaille, Diane; Keeling, Stephanie; et al.
<x xml:space="preserve">Abstract</x> Objective Cardiovascular disease (CVD) is a leading cause of mortality in rheumatoid arthritis (RA). This study systematically reviewed and appraised guidelines and quality indicators (QIs) pertaining to CVD risk management in patients with RA. Methods Four electronic medical databases (Medline, Embase, CINAHL, and Web of Science) and gray literature publications were searched using terms and keywords pertaining to guidelines, QIs, RA, and CVD (RA and general population literature searched). Abstracts were screened for inclusion and rated using the Appraisal of Guidelines for Research and Evaluation II instrument independently by 2 of 3 reviewers. Results In total, 16, 064 abstracts were screened and 808 underwent full‐text review. A total of 17 guidelines and 3 QI sets published between 2008 and 2013 were included. A number of consistent themes emerged, including the increased CV risk faced by RA patients and the need to address modifiable risk factors on a regular basis. The role of the multidisciplinary team in risk optimization was also highlighted. Ten guidelines provided recommendations for CVD prevention in patients with RA. Unfortunately, most recommendations lacked the specificity required to determine adherence to the recommendation. Only 4 RA‐specific CVD QIs were identified (1 general comorbidity screening, formal CVD risk estimation, exercise, and minimizing steroid use). Conclusion Regular screening for CVD risk factors is an important part of care in patients with RA. Unfortunately, existing RA‐specific CVD QIs do not adequately address risk factor management, and existing guideline recommendations lack specificity for measurement and use in quality improvement initiatives.